The Proportion of Acute Transfusion Reaction at Outpatient Blood Transfusion Unit in Tertiary Hospital in Indonesia - Zein, Ahmad Fariz Malvi Zamzam; Sukrisman, Lugyanti (Jurnal Penyakit Dalam Indonesia, 2020)
Introduction. Acute transfusion reaction (ATR) is an important issue related to patient safety. The prevalence of ATR at tertiary hospital in Indonesia is 0.5%. This study was aimed to determine the proportion of ATR in outpatient blood transfusion unit at tertiary hospital. Method. This retrospective study implemented data from medical records of adult patients who underwent blood transfusion in outpatient blood transfusion unit, Cipto Mangunkusumo Hospital between August – October 2014. The blood components included packed red cells (PRC), thrombocyte concentrate (TC), fresh frozen plasma (FFP), and cryoprecipitate. We recorded the administration of premedication and ATR-related symptoms/signs. The ATR report was based on WHO classification. Results. There were 1,010 blood transfusions during the study period. The distribution of blood components were PRC (n=802, 79.4%), PC (n=74, 7.3%), FFP (n=43, 4.3%), and cryoprecipitate (n=91, 9.0%). The premedication was administered in 21 transfusions (2.1%). There were 11 ATRs with WHO category 1 (1.1%), no other categories were reported. Based on blood component, the ATR occurred predominantly in PRC transfusion (0.6%), followed by FFP (0.3%), cryoprecipitate (0.1%), and TC (0.1%), respectively. Conclusion. The proportion of ATR in outpatients blood transfusion unit at Cipto Mangunkusumo Hospital was 1.1%. All reported ATR were category 1 in this study. The ATR was predominantly in PRC transfusion.